DIFFERENCES BETWEEN THE RELATIONSHIP OF INTEGRITY AND LEADERSHIP STYLES ACCORDING TO THE MODEL OF BERNARD BASS - FLORINA GUADALUPE ARREDONDO TRAPERO (Estudios Gerenciales, 2010)
This article aims to prove empirically that there are signifi cant differences in the correlation that shows no leadership, transactional leadership and transformational leadership (MLQ) with the perceived lack of integrity of the leader (PLIS). It also sought to test whether there was an increased intensity of the relationships between each of the variables of leadership with integrity (T-test). The results show that both transformational leadership and transactional relationship are directly related to integrity. Also based on the empirical results of this investigation is concluded that the relationship of transformational leadership with integrity is stronger than the relationship of leadership with transactional integrity. And that transactional leadership is in turn associated with more integrity that no lead.